The impact of institutional environment and ownership concentration on earnings quality: empirical evidence from European listed firms - Paiva, I.; Lourenço, I. (European Accounting Association Annual Congress, 2012)
In this paper we use panel data methodology to examine the relationship between ownership concentration and other firms´ characteristics for non-financing listed firms from the United Kingdom, France and Germany, that adopted IFRS. Considering the importance of legal system in influencing accounting practices, we find different level of earnings management between countries. Our findings suggest that legal systems and investor protection are likely to influence the relationship between ownership concentration and earnings management. Next, there is clear evidence that ownership concentration affects earnings management in Europe. We find a significant relationship between ownership concentration and discretionary accruals, which indicates that firms with a high level of insider ownership have less earnings management.